2019
DOI: 10.1177/1937586719856009
|View full text |Cite
|
Sign up to set email alerts
|

Developing Evidence-Based Design Guidelines for Medical/Surgical Hospital Patient Rooms That Meet the Needs of Staff, Patients, and Visitors

Abstract: Objectives: This research investigated medical/surgical (Med/Surg) patient room design to accommodate the needs of hospital staff, while at the same time accommodating the needs of patients and their visitors. Background: Designing hospital patient rooms that provide a comfortable healing experience for patients, while at the same time meeting the needs of the hospital staff, is a challenging process. Prior research has shown that many hospital patient room designs adversely affect the ability of hospital staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
0
23
1
1
Order By: Relevance
“…Since no interactions here were significant, the interpretation is that patients would choose for a situation where they would be able "to hear" or "stay connected with" the hallways. This finding diverges from what Patterson et al (2017) reported using a simulated room combined with printed room layouts to highlight differences. Their results lend support to the interpretation that visibility of the hallway, in the current study the open door, was important to provide them with a sense of safety and security, However, whereas they found mixed perceptions as to whether or not people preferred the use of a privacy curtain, we found that people preferred an open door irrespective of the level of privacy corroborating their report of participants' need to stay connected to people and the outside world.…”
Section: Safety and Privacy Versus Connectingcontrasting
confidence: 99%
“…Since no interactions here were significant, the interpretation is that patients would choose for a situation where they would be able "to hear" or "stay connected with" the hallways. This finding diverges from what Patterson et al (2017) reported using a simulated room combined with printed room layouts to highlight differences. Their results lend support to the interpretation that visibility of the hallway, in the current study the open door, was important to provide them with a sense of safety and security, However, whereas they found mixed perceptions as to whether or not people preferred the use of a privacy curtain, we found that people preferred an open door irrespective of the level of privacy corroborating their report of participants' need to stay connected to people and the outside world.…”
Section: Safety and Privacy Versus Connectingcontrasting
confidence: 99%
“…The remaining two interventions focus patient room bathroom doors, where we propose improved use of grab bars in patient bathrooms, adding additional and/or relocating existing grab bars in accordance with best practice guidelines. Grab bars were a potential intervention mentioned by multiple interviewees in the transcript analysis and have a strong backing to indicate their efficacy (Lavender et al 2020).…”
Section: Interventionsmentioning
confidence: 99%
“…To best support the capabilities and limitations of patient tasks in patient rooms, it is imperative to establish a baseline understanding about which design principles and features should therefore be prioritized, from multiple points of view. There has been an increasing awareness about the diverse views of stakeholders to inform the design process [16][17][18][19]. While it is certainly necessary to gather empirical data about patients using a prototype design to inform a proactive approach for safety, it is also important to address the assumptions made by those designing the room.…”
Section: Introductionmentioning
confidence: 99%